Status of Smooth Indian Otter (Lutra perspicillata) in Punjab - Singh, Gurmit (Indian Forester, 1991)
Three of the four species of otters occurring in Asia are reported in Punjab State. One of these, the Smooth Indian Otter is found in Harike Lake in Punjab. The lake habitat is threatened by a number of factors like excessive fishing, human encroachment and proliferation of water hyacinth. The author points to the need for further research on Indian otters to evolve an integrated programme.